The Power of Deeds: The Untold Story of Abdul Kadir Shamsuddin, by Khadijah Md Khalid, Shakila Yacob & Sharifah Mariam Alhabshi - Ku Boon Dar (Kajian Malaysia, 2020)
The book The Power of Deeds: The Untold Story of Abdul Kadir Shamsuddin outlines Abdul Kadir’s inspirational and magnanimous contributions towards Malaysia’s development. The biography’s publication is a serious endeavour by authors Khadijah Md Khalid, Shakila Yacob and Sharifah Mariam Alhabshi to document and illuminate the important role Abdul Kadir played in the country’s public administration. In particular, the biography sheds light on Abdul Kadir’s career path from his humble beginnings in the civil service, up to Abdul Kadir becoming the Chief Secretary to the Government of Malaysia. The position of Chief Secretary to the Government is the most senior officer in the Malaysian Civil Service and entails huge responsibilities in tandem with its primary position in the country’s administrative structure. The role of the Chief Secretary is akin to a “territorial boundary” between the executive body, which draws up the country’s policies and the administrative officers who enforce those policies. The Chief Secretary provides professional advice to the government regarding the feasibility of and necessity for a policy. This is important in ensuring there is no deviation and breach in enforcing the country’s policies. Hence, cooperation and tolerance between the Chief Secretary to the Government and the parties which shape and form the government is crucial in ensuring administrative competency and keeping the country on the right track.